Adoption of sustainable fuels and renewable energy in logistics: Examining the role of stakeholder theory in supply chain strategy. - Chukwudi Christian Ifekanandu; Chiemelie Benneth Iloka; Grace Ifeoma Anukwe; Jude Obinna Eze; Innocent Vitus Uwakwe; Samuel Asagba (PLoS ONE)
In contemporary society, sustainability is a key issue that borders on overall human existence, and it has been rigorously argued that extensive efforts are needed to ensure the survival of the human race. Such efforts include corporate bodies changing the ways they operate to ensure that their activities do not yield negative impacts on the environment and the human race in general. In view of this, this research was conducted to assess the influence of stakeholder theory (consumers' demand, suppliers' collaboration, and regulatory pressure) on the decision of companies in the logistics sector to adopt sustainable fuel and renewable energy in their operations. The study also sought to assess the mediating role of organisational commitment. To this end, 294 responses were gathered across companies in three states in Nigeria. Gathered data were analysed using SPSS and SmartPLS software. Findings indicate that stakeholder theory (consumers' demand, suppliers' collaboration, and regulatory pressure) yields significant influence on the adoption of sustainability measures (sustainable fuel and renewable energy) in logistics companies. Additionally, organisational commitment was found to mediate this relationship. Therefore, it was concluded that stakeholders should put pressure on logistics companies to adopt sustainability measures because they yield significant influence on that decision.